2005
DOI: 10.1063/1.1868872
|View full text |Cite
|
Sign up to set email alerts
|

Origin of ferromagnetism in Fe- and Cu-codoped ZnO

Abstract: Fe- and Cu-codoped ZnO was previously reported as a room-temperature dilute magnetic semiconductor. We have investigated the origin of the ferromagnetism in Zn0.95−xFe0.05CuxO using the zero-field Fe57 nuclear magnetic resonance and neutron diffraction. These measurements reveal that some Fe ions of Zn0.95−xFe0.05CuxO form a secondary phase, ZnFe2O4. Detailed comparison of nuclear magnetic resonance spectra of Zn0.95−xFe0.05CuxO, bulk ZnFe2O4 with normal spinel structure, and nanocrystalline ZnFe2O4 with inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(70 citation statements)
references
References 13 publications
3
65
2
Order By: Relevance
“…that the RT FM in this system is intrinsic, in accordance with the previous work [7]. It should be noted that, additional Cu doping has not induced obvious change in ferromagnetism of Zn-Fe-O system at 300 K, but rather caused a small increase in M only at 10 K. It means that additional Cu doping has a little effect on ferromagnetism of Zn-Fe-O system, but not very crucial as mentioned in [4].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…that the RT FM in this system is intrinsic, in accordance with the previous work [7]. It should be noted that, additional Cu doping has not induced obvious change in ferromagnetism of Zn-Fe-O system at 300 K, but rather caused a small increase in M only at 10 K. It means that additional Cu doping has a little effect on ferromagnetism of Zn-Fe-O system, but not very crucial as mentioned in [4].…”
Section: Resultssupporting
confidence: 75%
“…It is deemed that additional Cu doping is essential to achieve RTFM in Fe-doped ZnO bulk samples [3]. Howerver, Shim et al found that the ferromagnetism in Feand Cu-codoped ZnO stems from the secondary phase ZnFe 2 O 4 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Impurity atoms also contribute to visible emission; e.g., green luminescence from Cu acceptors in ZnO [13]. Shim et al [14] prepared the Cu, Mn co-doped ZnO samples with ferromagnetic property at room temperature, but the results showed that the ferromagnetism originated from the secondary phase of Zn Mn 2 O 4 . Previous work reported on a study of the oxygen sensing properties of Cr doped (1 at.%) and undoped ZnO [15] fabricated by reactive RF co-sputtering.…”
Section: Introductionmentioning
confidence: 98%
“…So far, the most popular mechanisms of the magnetic ordering for the ZnO related materials are carrier mediated exchange [15], using the bound magnetic polaron model based on the defects such as oxygen vacancy and Zn interstitial [16]. At the same time, some groups have pointed out that the ferromagnetism might be caused by the secondary phase rather than the substitution of the TM ions into the Zn site [17]. Recent reports about the observation of the room temperature (RT) ferromagnetism in copper doped ZnO materials have attracted great interest by the scientific community.…”
Section: Introductionmentioning
confidence: 99%